Research and numerical analysis on performance optimization of photovoltaic-thermoelectric system incorporated with phase change materials. (15th January 2023) - Lv, Song; Yang, Jiahao; Ren, Juwen; Zhang, Bolong; Lai, Yin; Chang, Zhihao
Abstract: In recent years, photovoltaic (PV) cells have been widely used to cope with the problem of global energy shortage. In the current researches, the PV-TEG-PCM (photovoltaic-thermoelectric generator-phase change material) system can improve the utilization of solar energy and the hybrid system shows better performance. Most of the previous studies were two-dimensional models or steady-state models, which could not accurately evaluate the system performance under fluctuating solar irradiation. This research constructs a three-dimensional thermal simulation transient model of the PV-TEG-PCM system. The model is simulated under fluctuating solar irradiation, model validity has been verified. This research completes and optimizes the theoretical researches of PV-TEG-PCM systems. This research will play a guiding role in the subsequent practical experiments and applications. The effects of PCM melting temperature, thickness and thermal conductivity are studied. The results show that the performance of PV-TEG-PCM system is better than that of PV-TEG or sole PV systems. At the peak sun-hour, the PV temperature was reduced for three types of PV-TEG-PCM systems compared to PV-TEG systems. Through simulation, the PCM layer with 30 mm thickness and melting temperature of 42 °C, can make the PV-TEG-PCM system established this time achieve the best thermal performance. Highlights: An unsteady three-dimensional numerical model of the PV-TEG-PCM system is developed. PV-TEG-PCM system has better performance than PV system and PV-TEG system. The influence of relevant parameters of PCM on the hybrid system is presented. 30 mm thick PCM layer achieves the best performance for this hybrid system.